2015
DOI: 10.18632/oncotarget.6126
|View full text |Cite
|
Sign up to set email alerts
|

Akt inhibition improves irinotecan treatment and prevents cell emergence by switching the senescence response to apoptosis

Abstract: Activated in response to chemotherapy, senescence is a tumor suppressive mechanism that induces a permanent loss of proliferation. However, in response to treatment, it is not really known how cells can escape senescence and how irreversible or incomplete this pathway is. We have recently described that cells that escape senescence are more transformed than non-treated parental cells, they resist anoikis and rely on Mcl-1. In this study, we further characterize this emergence in response to irinotecan, a first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…We have recently described that subpopulations of colorectal cells can escape CIS and resume proliferation 7 , 8 , 11 . This was confirmed in this study using either colorectal cut at colo-rectal with the pdf margin instead of color-ectal (LS174T) or breast (MCF7) cancer cells that entered senescence when treated respectively with sn38 or doxorubicin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently described that subpopulations of colorectal cells can escape CIS and resume proliferation 7 , 8 , 11 . This was confirmed in this study using either colorectal cut at colo-rectal with the pdf margin instead of color-ectal (LS174T) or breast (MCF7) cancer cells that entered senescence when treated respectively with sn38 or doxorubicin.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, phosphatase and tensin homolog (PTEN) depletion reverses established senescence induced by the BRAF oncogene and this leads to tumor progression 4 . In colorectal cancer, we have recently described two models of senescence escape, in response to oncogene 5 , 6 or during chemotherapy-induced senescence (CIS) 7 , 8 . In both cases, we have observed that a subpopulation of cells escapes this arrest and emerges as a more aggressive, dividing population.…”
Section: Introductionmentioning
confidence: 99%
“…These deleterious effects are not limited to carcinogenesis. We and others have also shown that these arrested cells and the proteins they secrete play a key role in chemotherapy resistance, allowing the generation of more aggressive cells in response to genotoxic treatments . For instance, important results indicate that Wnt activation induces the dedifferentiation of senescent cells, the reactivation of cell cycle progression, and the generation of subpopulations with higher tumor initiation potential .…”
Section: The Senescence‐associated Secretory Phenotypementioning
confidence: 95%
“…In this condition, we and others have shown that senescence relies on p21waf1 and it is not obvious that this protein is always acting as an inhibitor of cancer progression. Using different experimental models, we have shown that cancer cells enter senescence in response to chemotherapy but that persistent cells are able to escape this suppressive arrest . Senescence escape leads to the emergence of more transformed clones with enhanced potential for migration.…”
Section: Different Outcomes For Different Senescence Typesmentioning
confidence: 99%
“…We and others have shown that this suppression functions as an adaptive mechanism in response to chemotherapy-induced -senescence (CIS) (7,9). We have described that cancer cells can escape senescence and emerge as more transformed cells that resist anoikis and are more invasive (14)(15)(16)(17). In addition, we have also shown that cells having an incomplete senescence response are characterized by a reduced expression of CD47 (17).…”
Section: Introductionmentioning
confidence: 93%